Analisis Pembangunan Infrastruktur Terhadap Pertumbuhan Ekonomi Kota Mataram Tahun 2013-2022 - Triyatni, Diandini; Harsono, Iwan; Endang Astuti; Himawan Sutanto; Ida Ayu Putri Suprapti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The purpose of this study is to analyze the development of road infrastructure, water infrastructure through the distribution of clean water, and educational infrastructure both partially and simultaneously on the economic growth of Mataram City from 2013 – 2022. The data source comes from Badan Pusat Statistik of city of Mataram with secondary data as a type of data. The data processing technique that we used is multiple linear regression analysis through a program. The research findings show that Educational infrastructure as an independent variable partially has a positive and significant effect on the economic growth of the city Mataram. Meanwhile, clean water infrastructure has an insignificant negative effect and road infrastructure has an insignificant positive effect on the economic growth of Mataram City. Research show that economic growth in the Mataram City, in the 10 year period 2013 – 2022 does not show a large influence from the variables of road infrastructure, clean water and education infrastructure.